A review on factors impinges computer usage in education - Samy, Naresh Kumar; Che Rose, Raduan; Alby, Jeffrey Lawrence D'Silva (Science Publications, 2008)
The growing body of literature associated with educational computer use had examined numerous variables and interrelationships in order to gain a better understanding of computer beliefs and use of computers within education. Teachers’ computer acceptance is an important factor to the successful use of computers in education. Thus it is significant to draw attention to the factors affecting teachers’ computer use and its implications to teachers’ professional development strategies. This article would be useful for future researchers who are seeking directions to further examine the determinants of computer technology acceptance and its utilization based on the technology acceptance model.